Swaledale : Valley of the Wild River. - Fleming, Andrew (Oxbow Books, 2010)
This is a reprint of the first edition, published in 1998 by Edinburgh University Press. Now with an updated preface and colour illustrations throughout, this beautiful book tells the story of Swaledale, a well-loved part of the North Yorkshire Pennines. It shows how the perspectives of archaeology, history and ecology can be linked to transform our understanding of the landscape. Starting from the contemporary framework of the landscape with its stone walls, field barns and hay meadows - characteristic features which seem to reflect a way of life which has been here since time immemorial - th.